2020
DOI: 10.21203/rs.3.rs-62758/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling COVID-19 with Human Pluripotent Stem Cell-Derived Cells Reveals Synergistic Effects of Anti-inflammatory Macrophages with ACE2 Inhibition Against SARS-CoV-2

Abstract: Dysfunctional immune responses contribute critically to the progression of Coronavirus Disease-2019 (COVID-19) from mild to severe stages including fatality, with pro-inflammatory macrophages as one of the main mediators of lung hyper-inflammation. Therefore, there is an urgent need to better understand the interactions among SARS-CoV-2 permissive cells, macrophage, and the SARS-CoV-2 virus, thereby offering important insights into new therapeutic strategies. Here, we used directed differentiation of human pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Interestingly, flow cytometry measurements of the human peripheral blood-derived immune cells revealed little or no expression of ACE2, while high expressions were reported in human tissue macrophages, such as alveolar macrophages, liver Kupffer cells, and brain microglia [45]. Other studies have reported expression of ACE2 in alveolar macrophages and human monocyte THP-1 cells [46]. Studies to further determine the roles of ACE2 in spike glycoprotein S1-induced inflammation are therefore needed.…”
Section: Pharmacological Modulation Of Cytokine Hypersecretion In Coronavirus Infectionsmentioning
confidence: 99%
“…Interestingly, flow cytometry measurements of the human peripheral blood-derived immune cells revealed little or no expression of ACE2, while high expressions were reported in human tissue macrophages, such as alveolar macrophages, liver Kupffer cells, and brain microglia [45]. Other studies have reported expression of ACE2 in alveolar macrophages and human monocyte THP-1 cells [46]. Studies to further determine the roles of ACE2 in spike glycoprotein S1-induced inflammation are therefore needed.…”
Section: Pharmacological Modulation Of Cytokine Hypersecretion In Coronavirus Infectionsmentioning
confidence: 99%
“… 42 Caragana extract along with Kobophenol A is also used for chronic bronchitis in the form of a daily decoction, without any toxicity. 43 SARS-CoV-2 can trigger an excessive immune response known as cytokine storm, which can lead to multiple organ failure and death because of the inflammation 44 of the organs. The additional anti-inflammatory, bronchodilator, cardioprotective, and antioxidant activities of Kobophenol A can be an additive health benefit for COVID-19 patients and may potentially help to reduce mortality in COVID-19 patients.…”
mentioning
confidence: 99%
“…Protective phase in which immune responses especially adaptive immune responses have important roles in elimination of the virus at early stages of the disease. Damaging phase in which immune responses can also cause tissue damage via release of pro-inflammatory cytokines at severe stages (Duan et al, 2020). In severe conditions, excessive and uncontrolled production of pro-inflammatory cytokines including IL-6, IL-1, and TNF-α results in convergence of immune cells and leads to systemic inflammatory response, known as cytokine storm.…”
Section: Immune System Response and Cytokine Storm In Covid-19mentioning
confidence: 99%